The deformation energy and fission barriers of heavy nuclei - Ivanyuk F.A. (EPJ Web of Conferences, 2012)
The macroscopic part of the fission barriers of medium and heavy nuclei is calculated looking for the minimum of liquid drop energy at fixed volume and elongation without using any shape parameterization. The fission barrier heights, obtained within the Lublin-Strasbourg Drop model, are approximated by a simple analytical expression as functions of Z and (N – Z)/A only. In addition, using the topological theorem by Myers and Świa¸tecki which allows to represent the barrier height as the sum of the ground state microscopic correction (which is calculated and tabulated for all nuclei) and the liquid–drop fission barrier, we propose a simple but quite accurate approximation of the fission barrier heights.